ENGLISH IN A MULTILINGUAL CLASSROOM: A MINI-ETHNOGRAPHY STUDY AT BPK PLUS PENABUR CIREBON - Amelia Christianti Hutagaol; Dwi Nopiyadi; Lili Sururi Asipi (NextGen Education Review Journal, 2025)
This study aims to analyze the use of English in the context of multilingual classrooms at BPK Plus Penabur Cirebon Junior High School. The focus of the study is on student interaction patterns, factors that influence the use of English, and the linguistic dynamics that are formed in the learning process. This study uses a qualitative approach with a mini-ethnographic design. Data were collected through classroom observation, interviews with teachers and students, and documentation. Data analysis was carried out through the stages of reduction, categorization, and interpretation to find patterns of language use in classroom interactions. The results show that the use of English is influenced by students' linguistic backgrounds, social contexts, and teachers' pedagogical strategies. Translanguaging practices emerged as the dominant communication strategy that aided conceptual understanding and increased student participation. These findings are relevant for the development of English language learning strategies in multilingual environments, the formulation of school language policies, and the strengthening of EFL curricula. This study contributes new insights into understanding the practice of English language use at the junior high school level through a mini-ethnographic approach, which has rarely been used in the Indonesian context.